Financial Corrections on Public Procurement as a Corrective Mechanism for Protection of Public Budget Expenditure - Tsvetkova, Stanislava (Research Papers, 2021)
The article aims to analyze financial corrections in public procurement as one of the main corrective mechanisms for protection of public budget expenditures. To achieve this goal, three tasks have been performed: 1) Preventive and corrective mechanisms for protection of public expenditures are presented; 2) The organization of the control mechanisms regarding the public procurements and the imposition of financial corrections in Bulgaria is revealed and 3) the contribution of two international organizations to the topic is outlined - the Organization for Economic Cooperation and Development and the World Bank. The research methods used are historical-logical analysis and content analysis. The result of the research is a critical analysis and summary, which complement the Bulgarian analytical literature in the field.
Keywords: Public procurement; Financial corrections